Pemberdayaan Purna Tenaga Kerja Wanita melalui Pemanfaatan Pekarangan dan Pengolahan Jahe Menjadi Produk Bernilai Ekonomi - Mercy Bientri Yunindanova; Mth. Sri Budiastuti; Trijono Djoko Sulistyo (Abdihaz: Jurnal Ilmiah Pengabdian pada Masyarakat, 2020)
Empowerment of the Former of Female Migrant Workers through Garden Utilization and Ginger Processing into Economic Value Products A number of the productive women in Desa Kadirejo of Kabupaten Semarang have to work as female migrant workers (FMWs) who working abroad. Although this choice is economically profitable, these conditions also emerge several negative impacts on the family and society. Woman role as a wife and a mother becomes less optimal. Moreover, having finished as FMW, generally, most of the women were lack of productive skills. Thus, this program aimed to empower the former of FMWs through the optimization of home gardens and ginger processing to become economic value products. This activity was conducted in Desa Kadirejo, Kabupaten Semarang, Jawa Tengah, from July to September 2019. The steps of the activity were the problem and potential observation; socialization about the potential of home garden and cultivation method; vegetable cultivation practices and providing vegetable seeds; processing instant herbal from ginger; packaging and labeling training; and training of marketing mix. This activity was significantly able to provide life skills for the former of FMWs. The participants produced the ginger instants product, which was readily sold. Also, the former of FMWs had a skill for managing the home garden. In conclusion, by utilizing local resources, the former FMWs will be able to develop a business tant could support family finances without leaving the promary responsibility as wife and mother.